Continuous Wave and simulated GSM exposure at 1.8 W/kg and 1.8 GHz do not induce hsp16-1 heat-shock gene expression in Caenorhabditis elegans - Dawe, Adam S.; Nylund, Reeta; Leszczynski, Dariusz; Kuster, Niels; Reader, Tom; de Pomerai, David I. (Wiley, 2008)
Recent data suggest that there might be a subtle thermal explanation for the apparent induction by radiofrequency (RF) radiation of transgene expression from a small-heat-shock-protein (hsp16-1) promoter in the nematode, Caenorhabditis elegans. The RF fields used in the C. elegans study were much weaker (SAR 5-40 mW kg-1) than those routinely tested in many other published studies (SAR ~2 W kg-1). To resolve this disparity, we have exposed the same transgenic hsp16-1::lacZ strain of C. elegans (PC72) to higher intensity RF fields (1.8 GHz; SAR ~1.8 W kg-1). For both continuous wave (CW) and Talk-pulsed RF exposures (2.5 h at 25C), there was no indication that RF exposure could induce reporter expression above sham control levels. Thus, at much higher induced RF field strength (close to the maximum permitted exposure from a mobile telephone handset), this particular nematode heat-shock gene is not up-regulated. However, under conditions where background reporter expression was moderately elevated in the sham controls (perhaps as a result of some unknown co-stressor), we found some evidence that reporter expression may be reduced by ~15% following exposure to either Talk-pulsed or CW RF fields.